Pengaruh Persepsi Resiko dan Persepsi Kegunaan terhadap Niat Menggunakan Fintech - Herie Darmawan (Universitas Tarumanagara, 2022)
The purpose of this study is to verify a model of the relationship between perceived risk and perceived usefulness on the intention to use fintech with the theoretical approach of Technology Acceptance Model (TAM), Perceived Risk, and Financial Technology. The source of the data used is primary data, which is obtained directly from the respondents by using an online questionnaire in the form of a Google Form. The sample size is 202 users of banking and startup services and domiciled in Greater Jakarta. The method of determining the sample uses non-probability sampling. This study uses multiple regression methods with Smart PLS version 3. The results of this study indicate that Perceived Risk and Perceived Usefulness have a positive effect on Intention to Use Fintech Services. Tujuan penelitian ini adalah untuk memverifikasi suatu model hubungan perceived risk dan perceived usefulness terhadap intention to use fintech dengan pendekatan teori Technology Acceptance Model (TAM), Perceived Risk, dan Financial Technology. Sumber data yang digunakan adalah data primer, yang didapatkan langsung dari responden dengan menggunakan kuesioner online berupa Google Form. Ukuran sampel adalah 202 orang pengguna layanan perbankan dan startup serta berdomisili di Jabodetabek. Metode penentuan sampel menggunakan non-probability sampling. Penelitian ini menggunakan metode regresi berganda dengan program SmartPLS versi 3. Hasil penelitian ini menunjukkan bahwa Perceived Risk dan Perceived Usefulness berpengaruh positif terhadap Intention to Use Fintech Services.